Awareness of Cancer among Adolescent Students at Selected Schools of Bharatpur Metropolitan City, Chitwan - Koirala, Sushila; Thapa, Chitramaya; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2025)
Background Cancer is a major global health problem affecting the population of all age groups and it is the second leading cause of deaths globally. As one third of cancers are potentially preventable, awareness on cancer plays an effective role to avoid risk factors, detect the warning signs earlier and apply preventive measures on time. So, this study was conducted to assess awareness regarding cancer among adolescents. Methods A cross-sectional study design was carried among 154 adolescent students to assess awareness regarding cancer. Samples were students studying in grade 10 selected using non-probability purposive sampling technique from two government schools of Bharatpur Metropolitan. Self-administered structured questionnaire was used for data collection and analyzed by using descriptive statistics through Statistical Package for Social Science (SPSS) Version 16. Results Mean age of respondents was 15.33 years and more than half (53.2%) were female. Only 5.8% of respondents had history of cancer in their family. The study findings summarized the level of knowledge into three categories where, more than three-fifth (63%) had moderate level of awareness, 28.6% had low level of awareness and only8.4% had high level of awareness on cancer. Conclusions Though majority of the respondents had moderate level of knowledge regarding cancer but there is still awareness gap in the context of risk factors, warning signs and cancer screening. So, concerned authorities should make strategic plan on cancer awareness programme, add contents in school curriculum to increase the awareness of cancer among the adolescent students who are the key media for spreading their knowledge to public.